THE DEVELOPMENT OF TEACHING MATERIALS USING LEARNING CYCLE 5E TO INCREASE CRITICAL THINKING SKILLS AND STUDENT’S LEARNING OUTCOME OF HIGH SCHOOL STUDENTS ON THE SUBJECT OF REACTION RATE - Astrodjojo, Dwi Rosantika (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
The aim of research is to obtain the teaching materials based on Learning Cycle 5E Model that are feasible to increase the student?s critical thinking skill and learning outcome. The type of research is a developmental research because this research was to develop the teaching material consisting of lesson plan, student?s worksheet, and knowledge assessment instrument. The development of teaching materials was using four D model. The feasibility of teaching materials includes the validity, practicality, and the effectiveness. The data collecting used observation, test, and questionnaire method. The data analysis technique that is utilized is descriptive qualitative analysis and descriptive quantitative analysis. According to the observational data showed some finding as follows: (1) the validity of teaching materials were valid category; (2) the practicality of teaching material was shown by implementation of the lesson plan categorized as good, student?s based activity was dominant, and the obstacle in learning process could be solved; and (3) the effectiveness of the teaching materials shown by positive student?s response to implementation of learning process, developed critical thinking skill increased as high category, and the student?s learning outcomes on Gnostic aspect increased, the average student?s attitude aspect is B+ and the average of the student?s skill aspect was A-. Based on these result, it can be concluded that developed teaching materials using learning cycle 5E model are feasible to be used to increase critical thinking skills and students learning outcomes